2015
DOI: 10.1002/pola.27589
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 4‐fluorophenyl pendants in thieno[3,4‐b]thiophene‐benzo[1,2‐b:4,5‐b′]dithiophene‐based polymers on the performance of photovoltaics

Abstract: Polymers consisting of benzo[1,2‐b:4,5‐b′]dithiophene and thieno[3,4‐b]thiophene units (PTB‐based polymers), either fully or partially containing 4‐fluorophenyl pendants, are synthesized as electron donor materials for inverted‐type polymer solar cells (PSCs). The influence of the 4‐fluorophenyl pendant content on the thermal and optical properties, the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO), the hole mobilities, and photovoltaic performances are investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Recently, we have developed a series of PTB‐based polymers, which have p ‐substituted phenyl ester pendants in their TT repeating units, and found that their highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) energy levels can be efficiently controlled by varying the p ‐substituents on the phenyl rings . Additionally, PTB‐based ternary copolymers consisting of two types of TT components with 4‐fluorophenyl and n ‐octyl esters have also been synthesized, and precise control of the HOMO levels of the resulting polymers has been achieved by changing the feed ratio of two TT comonomers . When these ternary copolymers were used as electron donors in OPV devices, a higher open‐circuit voltage ( V oc ) was attained using the polymer with the deeper HOMO level.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have developed a series of PTB‐based polymers, which have p ‐substituted phenyl ester pendants in their TT repeating units, and found that their highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) energy levels can be efficiently controlled by varying the p ‐substituents on the phenyl rings . Additionally, PTB‐based ternary copolymers consisting of two types of TT components with 4‐fluorophenyl and n ‐octyl esters have also been synthesized, and precise control of the HOMO levels of the resulting polymers has been achieved by changing the feed ratio of two TT comonomers . When these ternary copolymers were used as electron donors in OPV devices, a higher open‐circuit voltage ( V oc ) was attained using the polymer with the deeper HOMO level.…”
Section: Introductionmentioning
confidence: 99%
“…The lower HOMO energy of PPhDOTFV compared to PPhDOTV originates from the strongly accepting nature of fluorine in the phenylene part of PPhDOTFV, which is beneficial for obtaining a higher V oc in BHJ OPVs. [19][20][21] The energy levels of the lowest unoccupied molecular orbital (LUMO) of PPhDOTV and PPhDOTFV estimated from their E g values and HOMO levels were situated at ¹3.48 and ¹3.68 eV, respectively.…”
Section: Synthesis and Fundamental Properties Of Pphdotv Andmentioning
confidence: 99%